If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 5p + -4 Reorder the terms: 16 = -4 + 5p Solving 16 = -4 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 16 + -5p = -4 + 5p + -5p Combine like terms: 5p + -5p = 0 16 + -5p = -4 + 0 16 + -5p = -4 Add '-16' to each side of the equation. 16 + -16 + -5p = -4 + -16 Combine like terms: 16 + -16 = 0 0 + -5p = -4 + -16 -5p = -4 + -16 Combine like terms: -4 + -16 = -20 -5p = -20 Divide each side by '-5'. p = 4 Simplifying p = 4
| (2d+6)(3d-15)=0 | | 32y^2-4y-1=0 | | 4(4x+3)= | | 5a+7=2a+1 | | b=2 | | x^2-x+564=23.78 | | x^2-x+564=64 | | x^2-x+564=10 | | 5a-3=17 | | x^2-9x+16=0 | | -8x-18=14 | | g^2-15g-54=0 | | 8h^2+9=38h | | 7n^2-14=-7 | | 7n^2+2n=0 | | 6w^2-23w+7=0 | | 5=10 | | 5x-20=2x-14 | | 4x-28=6 | | -5m^2=-500 | | 7m^2=-21 | | 2x+8y=-6 | | -10x+8y=64 | | 5x-15=4x+8 | | 0x+8y=-16 | | 12n+26=-10 | | (11x+2)+(6x-5)= | | 3-x=13 | | 4x-8=5x-10 | | 0=-0.02d^2+2.6d-66.5 | | 12-5x=-8 | | (11x+2)=(6x-5) |